THE EMERGENCE AND EVOLUTION OF THE MILITARY CLASS IN SOGDIANA: STRATEGIC NECESSITY AND SOCIETAL INTEGRATION (Conferencea, 2024)
The article is devoted to the study of the formation and evolution of the military class in Sogdiana in the early Middle Ages, considering its role in the political and social structure of the region. As a strategic center on the Great Silk Road, Sogdiana was subjected to numerous external invasions, which contributed to the development of a unique military class. The author analyzes historical documents, wall paintings, military titles and numismatic materials to identify key aspects of military organization and its influence on state governance. Particular attention is paid to such military ranks as "ispahbad", "akhvirpat" and "chor", their functions and evolution under the influence of the Turkic Khaganate. The study emphasizes the significance of the military class as an integral part of Sogdian social and political life, as well as the need for further interdisciplinary research to deepen the understanding of this phenomenon.